Textbook Analysis of Pancasila and Civic Education Class VIII and Curriculum 2013 in State Junior High School 4 Palu - Sukmawati Sukmawati; Jamaludin Jamaludin; Shofia Nurun Alanur; Fina Fatikhatus Solikhah; Rahmadani H. Dunggio; Marzella Dalla; Dewa Ayu Made Suryani; Abdy Evansyah; Fatima Az-Zahra; Tanti Tanti; Nirmaya Sasnita Sari; Husaena Almahdali; Nur Ainun (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the strategy of using teacher's and student's books for learning activities, to determine the suitability of the contents of teacher's books and student books with the demands of SKL, KI, and KD, to find out teacher's books and student books from the aspect of adequacy and depth of material, as well as its relation to themes and theme networks, and to find out the suitability of teacher's books and student books with the concept of a scientific approach. This research is a type of descriptive research with a qualitative approach. Qualitative research is methods to explore and understand the meaning obtained from a number of individuals or groups of people who are considered to originate from social or humanitarian issues. Analysis of teacher's books and student books of PPKn class VIII curriculum 2013 is very important to do in order to evaluate the success of learning PPKn. By analyzing the teacher's book, it can be seen whether the book provides clear and comprehensive guidance for teachers in teaching Civics. A good teacher's book should present clear learning objectives, structured teaching steps, and additional supporting resources. Student books and teacher books are a means of implementing the 2013 curriculum in the learning process. Curriculum is an activity carried out by schools in order to influence students in learning to achieve a goal. There are several benefits of textbooks including helping students in carrying out the curriculum because it is structured based on the applicable curriculum, being a teacher's guide in determining teaching methods, and providing opportunities for students to repeat lessons or learn new material.